2021
DOI: 10.3390/healthcare9060774
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise-Based Cardiac Rehabilitation on Left Ventricular Function in Asian Patients with Acute Myocardial Infarction after Percutaneous Coronary Intervention: A Meta-Analysis of Randomized Controlled Trials

Abstract: (1) Background: The effects of exercise-based cardiac rehabilitation (CR) on left ventricular function in patients with acute myocardial infarction (AMI) after percutaneous coronary intervention (PCI) are important but poorly understood. (2) Purpose: To evaluate the effects of an exercise-based CR program (exercise training alone or combined with psychosocial or educational interventions) compared with usual care on left ventricular function in patients with AMI receiving PCI. (3) Data sources, study selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“… Participants: All participants were post-PCI patients included in the meta-analysis. Intervention measure: The intervention measures in all studies were ER; five studies ( 34 , 36 , 39 , 43 , 45 ) did not provide details, one study ( 30 ) required plans including Baduanjin, and one study ( 38 ) required integration with traditional Chinese exercises. One study ( 42 ) required the inclusion of high-intensity interval training (HIIT).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Participants: All participants were post-PCI patients included in the meta-analysis. Intervention measure: The intervention measures in all studies were ER; five studies ( 34 , 36 , 39 , 43 , 45 ) did not provide details, one study ( 30 ) required plans including Baduanjin, and one study ( 38 ) required integration with traditional Chinese exercises. One study ( 42 ) required the inclusion of high-intensity interval training (HIIT).…”
Section: Resultsmentioning
confidence: 99%
“…LVEF: Twelve meta-analyses ( 30 – 33 , 37 – 40 , 42 45 ) assessed LVEF and the GRADE rating of these outcomes were 5/12 ( 31 , 32 , 40 , 43 , 44 ) considered high, 4/12 ( 30 , 33 , 37 , 42 ) considered moderate, and 3/12 considered low ( 30 , 31 , 45 ). The high and moderate evidence outcomes all showed that ER could improve the LVEF in patients after PCI, except one ( 34 ), which was meaningless ( p = 0.23) when comparing HIIT with MICT.…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis of RCTs by Yanijao et al shows a statistically significant improvement in the control group regarding left ventricular ejection fraction (LVEF), left ventricular end-diastolic dimension (LVEDD), and left ventricular end-systolic volume (LVESV) [ 16]. A study by Agnieszka et al shows that the exercise stress test time and the metabolic equivalent of task (MET), the maximal oxygen consumption (VO2max), and the sixminute walk test (6MWT) score increased significantly (p = 0.0001) [17].…”
Section: Figure 3: Key Components Of Cardiac Rehabilitationmentioning
confidence: 99%
“…Finally, completing the exercise training of a CR program is associated with an improvement in cardiorespiratory capacity measured by an increase in the METS achieved in the exercise stress test and has also been associated with an increase in LVEF [ 12 , 13 ]. Whether the improvements in function class and LVEF lead to a change in the low vs. no-low risk stratification (RS) and prognosis is substantially unknown.…”
Section: Introductionmentioning
confidence: 99%